Precision monitoring of kidney transplant health via cell-free DNA and RNA - Maya S. Schlesinger; Darshana M. Dadhania; John R. Lee; Iwijn De Vlaminck (Current Opinion in Organ Transplantation, 2026)
Purpose of review Cell-free nucleic acids (cfNAs) in plasma and urine have emerged as noninvasive biomarkers for monitoring kidney transplant health. This review summarizes recent advances in the development of cell-free DNA (cfDNA) and cell-free RNA (cfRNA) assays for immune and infection-related complications, and discusses their potential to enable precision monitoring of allograft health. Recent findings Large prospective multicenter studies have established donor-derived cfDNA as a robust biomarker of acute allograft rejection, with increasing evidence supporting the use of cfDNA for surveillance, prognostication, and integration with complementary molecular and clinical biomarkers. Metagenomic cfDNA assays enable broad detection of bacterial, viral, and fungal pathogens. More recently, cfRNA profiling has emerged as a complementary approach that captures tissue-type and cell-type-specific transcriptional activity, providing molecular insight into immune activation, tissue injury, and disease mechanisms. Urine cfRNA is particularly promising because of its enriched representation of kidney-derived transcripts. Summary Cell-free nucleic acid assays are reshaping the management of kidney transplant recipients by enabling noninvasive assessment of rejection, infection, and allograft injury. Continued advances in sequencing technologies, computational methods, and multimodal biomarker integration are expected to accelerate their clinical adoption and improve precision care for transplant recipients.